2016
DOI: 10.1016/j.celrep.2016.02.089
|View full text |Cite
|
Sign up to set email alerts
|

SMARCAL1 Resolves Replication Stress at ALT Telomeres

Abstract: In the originally published Supplemental Information file associated with this article, the Supplemental Experimental Procedures were inadvertently omitted. The Supplemental Information has now been updated online to include these additional experimental reagents and procedures. The authors apologize for the error and for any inconvenience that may have resulted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, they concluded that the function of SMARCAL1 was limited to ALT-positive cells (Cox et al , 2016). This group used two telomerase-positive cell lines with average telomere length possibly explaining why they did not observe a need for SMARCAL1 during telomere replication in telomerase-positive cells.…”
Section: Smarcal1mentioning
confidence: 99%
“…However, they concluded that the function of SMARCAL1 was limited to ALT-positive cells (Cox et al , 2016). This group used two telomerase-positive cell lines with average telomere length possibly explaining why they did not observe a need for SMARCAL1 during telomere replication in telomerase-positive cells.…”
Section: Smarcal1mentioning
confidence: 99%
“…Telomeric repeats are hard to replicate owing to the formation of abnormal DNA structures and/or stable protein complexes, as is evident form fork stalling that is comparable to or even stronger than at other microsatellite sequences [93,94]. As discussed above, stalled forks can be readily converted into 5 0 resected, one-ended DSBs via endonucleases involved in ALT [87,95]. Since telomeres are repetitive in nature, "out of register" strand invasion or multiple template-switching events can lead to lengthening of the repetitive sequence after BIR is complete.…”
Section: Alternative Lengthening Of Telomeres Mimics Large-scale Micrmentioning
confidence: 99%
“…Cells lacking SMARCAL1 are prone to accumulate DSBs [32] and patients with a biallelic deficiency in SMARCAL1 have the Schimke immunoosseous dysplasia (SIOD) disease that includes cancer predisposition [33,34]. It is interesting to note that SMARCAL1 is required to accurately and effectively replicate telomeric DNA [35][36][37]. This is the DNA of eukaryotic chromosomes that is predicted to be most sensitive to replication restart because a stalled replication fork at this location cannot be rescued by a convergent fork from another replication origin.…”
mentioning
confidence: 99%